(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
The paper studied the matters of solvability of the second order operator differential equations with multiple characteristics on the semi-axis. In the space of Sobolev type W2 2 (R+ ; H) identified conditions that ensured the unique and well-posed solvability are of the considered equation which is cleared by its operator coefficients